The phonetic structures of Hadza - Bonny Sands; Ian Maddieson; Peter Ladefoged (Studies in African Linguistics, 1996)
Hadza is one of three East African languages with clicks. Previous field repons on this language have disagreed on several of its phonetic chanacteristics, including the number and nature of the clicks. This paper-based on acoustic and aniculatory analyses of data collected in recent fieldwork-presents a more detailed picture than any previous work. Special attention is given to the articulation of the click types and the acoustic features of the click accompaniments, the role of aspiration in distinguishing classes of consonants, and the fonnant structure of vowels.